A new species of the genus Achalinus from southwestern Guangdong Province, China (Squamata: Xenodermatidae) - Wang, Jian; Li, Yao; Zeng, Zhao-Chi; Lyu, Zhi-Tong; Sung, Yik-Hei; Li, You-Yu; Lin, Chao-Yu; Wang, Ying-Yong (Zootaxa, 2019)
A new species of xenodermatid snake, Achalinus yunkaiensis J. Wang, Y. Li & Y.Y. Wang, sp. nov. was described based on a series of specimens collected from Dawuling Forestry Station located in the Yunkai Mountains of western Guangdong Province. It can be distinguished from known congeners by a significant genetic divergence at the mitochondrial CO1 gene fragment examined (p-distance ≥ 12.0%) and the following combination of characters: (1) dorsal scales strongly keeled, in 23 rows throughout the body, the most outer row on each side smooth and significantly enlarged; (2) tail relatively shorter, TaL/TL ratio 18.5–20.0%; (3) maxillary teeth 20–22; (4) length of suture between internasals subequal to that between the prefrontals; (5) nasal divided into two sections by nasal cleft, posterior one half as long as anterior; (6) loreal elongated, nearly twice as wide as high; (7) supralabials six; (8) infralabials six; (9) temporals 2+2+3 (rarely 2+2+4), the two anterior temporals in contact with eye; (10) ventrals 151–162, subcaudals 49–56 arranged in single row, not paired; (11) cloacal entire; (12) uniform brown (in adults) or black (in juveniles) above, tinged weakly iridescent, with a longitudinal dark-colored vertebral line; (13) light brown (in adults) or greyish white (in juveniles) beneath; and (14) dorsum with a longitudinal dark brown vertebral stripe from posterior margin of parietals to tail tip. Currently, 13 species are known in the genus Achalinus, with seven from mainland China.